Strategi Peningkatan Produktifitas Usaha Mikro Makanan Dan Minuman Di Kabupaten Jombang - Lina, Lina Susilowati; Shanti Nugroho, Shanti Nugroho; Celza Putri Amelia, Celza Putri Amelia (Rumah Jurnal, University of Jember, 2025)
Micro food and beverage businesses in Jombang Regency have great potential to be developed. The research problem is low productivity. The study aims to provide priority strategies for increasing the productivity of micro food and beverage businesses in Jombang Regency. The study uses an analytical descriptive approach, with the hierarchy process analysis (AHP) technique. The data collection method uses survey and interview techniques. Questionnaires given to 25 key persons consisting of academics and micro cullinary. The results show that the priority scale of the field is production as the main priority, marketing, institutions and human resources. In micro food and beverage businesses, production is the main priority because it is related to increasing production capacity through easy access to capital, increasing the variety of food and beverage products through innovation, increasing the efficiency of resource use and increasing the quality product